Assessment of trace heavy metals contamination in the tissues and saliva of the medicinal leech hirudinaria manillensis - Alaama, Mohamed; Abdualkader, Abdualrahman Mohammed; Ghawi, Abbas Mohammad; Merzouk, Ahmed; Khalid, Reem. S.; Helal Uddin, A.B.M. (Central Fisheries Research Institute of Turkey and Japan International Cooperation Agency (JICA), and published in English, 2021)
Concentrations of heavy metals (HMs) in the tissues and saliva extracts of leeches (Hirudinaria manillensis) collected from Cheneh Lake, Terengganu, Malaysia were investigated. Concentrations of HMs like Cadmium (Cd), Chromium (Cr), Iron (Fe), Manganese (Mn), Nickel (Ni), Lead (Pb), Selenium (Se) and Zinc (Zn) were revealed by utilising Inductively Coupled Plasma Mass Spectroscopy (ICP-MS). Nearly all the examined HMs concentrations in the lake water were noted to be higher compared to the Maximum Permissible Limits (MPL) as per Interim National Water Quality Standards for Malaysia (INWQS). Moreover, traces of HMs were discovered in tissues and saliva extracts of leeches. Such quantities may pose a health hazard to the patients upon an instant application of leeches on their skin. In this work, a novel technique was presented to decrease the level of metals in leech saliva by espousing a frequent washing process involving deionized or non-chlorinated water for three weeks. This process was extremely effectual in considerably decreasing HMs concentrations (P<0.05), particularly Cd level (up to 99.7%) in saliva and Pb level (up to 92.38%) in tissues. Thus, a constant washing process might aid in harmless utilization of leeches for different conventional biomedical practices.